2021
DOI: 10.3390/molecules26185682
|View full text |Cite
|
Sign up to set email alerts
|

Gas Plasma-Augmented Wound Healing in Animal Models and Veterinary Medicine

Abstract: The loss of skin integrity is inevitable in life. Wound healing is a necessary sequence of events to reconstitute the body’s integrity against potentially harmful environmental agents and restore homeostasis. Attempts to improve cutaneous wound healing are therefore as old as humanity itself. Furthermore, nowadays, targeting defective wound healing is of utmost importance in an aging society with underlying diseases such as diabetes and vascular insufficiencies being on the rise. Because chronic wounds’ etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 141 publications
(133 reference statements)
0
17
0
Order By: Relevance
“…Mainly in injured dogs and cats, but also studies with other pets have shown that the combination of NIPP with drugs leads to a significant improvement of wound healing. [30][31][32][33][34][35][36] The same was confirmed in wounded sheep. 37 Molecular analysis demonstrated that increased ROS concentrations were present in the wound area.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Mainly in injured dogs and cats, but also studies with other pets have shown that the combination of NIPP with drugs leads to a significant improvement of wound healing. [30][31][32][33][34][35][36] The same was confirmed in wounded sheep. 37 Molecular analysis demonstrated that increased ROS concentrations were present in the wound area.…”
Section: Discussionmentioning
confidence: 69%
“…However, there are some studies on the use of NIPP to treat wounds in different animal species. Mainly in injured dogs and cats, but also studies with other pets have shown that the combination of NIPP with drugs leads to a significant improvement of wound healing 30–36 . The same was confirmed in wounded sheep 37 .…”
Section: Discussionmentioning
confidence: 83%
“…The present study was Intended as a follow-up study to the data already described in Eggers et al 2022, in which we observed a stimulating effect of NIPP on proliferation and remodelling [ 30 ]. The proliferation-promoting effect of NIPP has also been described by other authors in in vitro [ 66 ], in vivo [ 67 ] and clinical studies [ 68 ], but the underlying mechanisms are still largely unknown. Our study demonstrates that anti-inflammatory effects are induced by NIPP even in the absence of an inflammatory state, with a simultaneous proliferation-promoting effect of NIPP.…”
Section: Discussionmentioning
confidence: 94%
“…Analyses were conducted using Stata/SE 14.2 (StataCorp., College Station, TX, USA). Graphs were produced using the ggplot2 software package [ 67 ] in R version 4.2.1 (R Core Team 2022, Vienna, Austria) [ 66 ] and prism 9.5.0 software (GraphPad, San Diego, CA, USA) for inflammation-related data analysis using paired t -test.…”
Section: Methodsmentioning
confidence: 99%